(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
A simple, specific and precise high performance liquid chromatographic method was developed and validated for simultaneous determination of Desvenlafaxine and Clonazepam in tablets. The chromatographic separation was performed using Hypersil ODS C18 Column (4.6 × 250 mm, 5μm particle size). The mobile phase consisted of a combination of acetonitrile and 0.05 M ortho phosphate buffer (pH 4.0) in the ratio of 60:40 v/v at a flow rate of 1.2 ml/min with the detection wavelength at 225 nm. Both the drugs showed good linearity in the concentration range of 60-140μg/ml and 0.6-1.4μg/ml respectively. The correlation coefficients were obtained as 0.996 and 0.997 respectively for Desvenlafaxine and Clonazepam. The retention times for Desvenlafaxine and Clonazepam were found to be 2.687 and 3.817 min respectively. The developed analytical method was validated for linearity, precision, accuracy, ruggedness, robustness, specificity and system suitability according to ICH guidelines. The developed method can successfully be employed for routine quality control of Desvenlafaxine and Clonazepam in combined tablet dosage forms.